Pengaruh Harga, Reputasi, Kualitas Jasa, Promosi, Keterpaksaan Berpindah, Dan Rekomensasi Pada Perilaku Nasabah Berpindah Bank - Pursetyaningsih Pursetyaningsih (Universitas Airlangga, 2008)
The aim of this research is to measure the effect of price, reputation, service quality, promotion, involuntary switching and recommendation to customer bank switching behavior. Customer switching behavior creates negative impact to market share, decreases profit, loss revenue and investment, and company must spend a lot of money to get new customer. This research based on Theory of Reasoned Action (Fieshbein dan Ajzen, 1980) with two modifications: 1). Critical incident factor that influence bank switching behavior for Asian market is pricing, reputation, promotion, involuntary switching, recommendation and using service quality as evaluation of core service failure, encounter service failure, and inconvenience. Service quality is also an evaluation for attitude toward switching. 2). Subjective norm reject from the model because: a). Attitude is strong predictor for behavior, subjective norm have multikolinearity with attitude. This research is confirmatory study, use survey method with questioners to 323 respondents in Indonesia. Validity for reflective variable use cross loading ≥ 0,7 as discriminant validity and AVE ≥ 0,5 as convergent validity. Reliability use composite reliability ≥ 0,7. Formative variable validity use content and face validity and weight and significantly of weight. The result of this research have Goodness of Fit Model is 0,3949. Pricing and recommendation significant positive influence attitude toward switching with p value of 0,009183. and 1,314E-05. Attitude toward switching is positive significant influence intention to switching with p value 2,7310E-23. Variable past switching behavior influences variable intention to switch directly and mediating by attitude toward switching with p value of 6,9267E-03 and 6,5522E-04. Add path from pricing and recomendation increasing goodness of fit model become 0,4053.